Wideband impedance characterization and modeling of electromagnetic interference filtering chokes - Jie, Huamin (Nanyang Technological University, 2024)
Faster switching power semiconductor devices have resulted in highly compact power converters with excellent conversion efficiency, which fits well with emerging applications, such as aircraft and electric vehicles. However, it also causes a significant increase in conducted electromagnetic interference (EMI) emissions, both in emission level and occupied bandwidth. To comply with the relevant EMI limits, EMI filters are the essential parts of power converter designs. A passive EMI filter is composed of several capacitors and inductors to achieve the required attenuation to control the conducted emissions below the applicable limits. To realize high inductance, all the EMI filtering chokes are wound on magnetic cores, and therefore their physical sizes are usually much larger than those of the capacitors. Due to the parasitic effect of a choke, its impedance at high frequencies can degrade the EMI filter attenuation. Therefore, accurate impedance information of a choke across a wide frequency band allows an EMI filter attenuation to be predicted with good confidence so that it avoids the usual trial-and-error approach adopted in the industry. Also, it prevents over-designing an EMI filter so that the filter’s size can be optimized. Based on accurate wideband impedance information of an EMI filtering choke, it facilitates the equivalent circuit construction so that it can be integrated with the circuit model of the converter for predicting the conducted emission. Therefore, the impedance characterization and modeling of EMI filtering chokes have become emerging research topics in power electronics. Most existing research works usually characterize the impedance of the chokes up to a few to tens of MHz. This frequency range is adequate for conventional electromagnetic compatibility (EMC) standards, such as CISPR-22, which covers from 150 kHz to 30 MHz. However, for aerospace applications, the DO-160 has an upper frequency limit of 152 MHz. Similarly, for automotive applications, the CISPR-25 calls for conducted emission tests up to 108 MHz. As mentioned earlier, the switching frequency of semiconductor power devices has been increasing from tens of kHz to almost a few MHz, producing conducted EMI emissions well above tens of MHz. In view of the gap, this thesis proposes several novel methods to characterize impedances of any EMI filtering chokes covering a wide frequency band, either through a direct measurement or numerical simulation approach. These methods are developed to realize the impedance characterization of various EMI filtering chokes accurately up to 120 MHz. With the known impedance information, the behavioral models of these chokes can be constructed accordingly for further circuit simulation purposes. The thesis starts with impedance characterization of single-phase common-mode (CM) and differential-mode (DM) chokes based on a two-port circuit de-embedding (TCD) method. It entails the design of unique fixture adapters to facilitate the electrical connection between the coaxial ports of a vector network analyzer (VNA) and the non-standard leaded terminals of these chokes. By extracting the parasitic parameters of fixture adapters via boundary-element analysis (BEA), the equivalent circuit of the measurement setup can be obtained and de-emended through the network analysis, achieving accurate measured impedance from 150 kHz to 120 MHz. For three-phase CM chokes (CMCs), two novel methods are proposed. The first one is based on a single-port circuit de-embedding (SCD) approach, which evolves from the circuit theory and removes the influence of fixture adapters through the BEA. It is highly versatile and can be implemented with either VNA or impedance analyzer (IA) but necessitates the de-embedding of fixture adapters for good measurement accuracy. The second one adopts a three-port network calibration (TNC) approach, which employs the three-port network theory and compensates the introduced parasitic parameters through a calibration process. It does not require the details of the fixture adapters but can only work with a four-terminal IA. For completeness, a numerical simulation method that integrates the FEA and mixed-mode theory is also developed for impedance characterization of both single- and three-phase CMCs up to 120 MHz. This enables both CM and DM impedance information of any choke to be extracted efficiently. While its precision may not match that of direct measurement methods, it can predict the impedance frequency responses prior to choke fabrication so that the choke design can be optimized. Based on the extracted impedance information, a behavioral modeling method is proposed to construct the equivalent circuits of single- and three-phase CMCs. The models are built based on the multi-stage RLC iteration circuits that take into account the frequency-dependent permeability of the magnetic core, such as the nanocrystalline core.